FIELD EFFICACY OF BRADYRHIZOBIUM JAPONICUM ISOLATES AND THEIR IMPACT ON CROP GROWTH, NUTRIENT CONTENT AND PRODUCTION OF SOYBEAN IN VERTISOL - F. C. AMULE,; A. K. RAWAT,; R. K. SAHU, (The Bioscan, 2015)
A field experiment was conducted at research station, JNKVV, Jabalpur (M.P.) during 2009-10 to test the efficacy of B. japonicum under field conditions and evaluates their impact on crop growth of soybean in vertisol. The said experiment was the field testing part of research which was conducted during 2002-2007. The efficacy of 36 isolates were tested and also compared with the USDA isolates, FUI (Fertilized uninoculated control) and UFUI (Unfertilized un inoculated control) in field condition. Results revealed that the maximum seed germination were observed with R 11 isolate (48 and 65%) followed by R 35 (46 and 63%) at 4 th and 5 th DAS. Similarly nodule number (66 plant -1 ), nodule ODW (0.36 g plant -1 ), nodule N (3.72%), grain yield (3350 kg ha -1 ) and total N uptake (429 kg ha -1 ) were recorded significantly superior over FUI. Only eight isolates could increase N content of plants at 45 days over FUI while phosphorus and potassium content were significantly higher only with R 11 (3.78, 0.085, 0.59 % NPK respectively) fallowed by R 35 (3.70, 0.082, 0.58% NPK respectively) over FUI. Rest of the isolates except BR 11 , R 12 , R 16 , R 17 , R 21 and R 35 were statistically at par to FUI toward their promise for seed yield.